TEKNIK RELAKSASI OTOT PROGRESIF MENURUNKAN SKALA KELELAHAN (FATIGUE) PADA PASIEN KANKER PAYUDARA - Harini Harini; Edi Purwanto; Arifin Hidayat (Jurnal Cakrawala Ilmiah, 2023)
Introduction :The incidence of fatigue in breast cancer patients is higher than in other types of cancer, namely around 33% of breast cancer patients experience fatigue after 5 years of treatment. Progressive muscle relaxation is a movement that aims to provide a relaxed physical feeling by tensing and relaxion the muscles in one part of the body at the same time. This study aims to identify the effect of progressive muscle relaxation techniques on fatigue in breast cancer patients. Method: Quantitative research type with pre experimental methods and one group pre post test design. A sample of 11 people was obtained using Consecutive Sampling techniques according to the inclusion and exclusion criteria. The instrument used to measure fatigue uses a standardized instrument, namely the Functional Assessment Chronic Illness Therapy (FACIT) scale questionnaire. Fatigue was measured before and after progressive muscle relaxation given for 3 days every morning and evening. Then the data was analyzed using the Paired T Test. Result: Obtained pvalue =0,000 (pvalue≤.0,05) with 95% significance. So there is an influence between providing progressive muscle relaxation and the level of fatigue in breast cancer patients. Conclusion: The progressive muscle relaxation technique is very effective in reducing fatigue in advanced breast cancer patients and can be done independently bacause this therapy is not difficult and does not require imagination and suggestion in its application.